2013
DOI: 10.1038/nature12825
|View full text |Cite
|
Sign up to set email alerts
|

Rare coding variants in the phospholipase D3 gene confer risk for Alzheimer’s disease

Abstract: Genome-wide association studies (GWAS) have identified several risk variants for late-onset Alzheimer's disease (LOAD)1,2. These common variants have replicable but small effects on LOAD risk and generally do not have obvious functional effects. Low-frequency coding variants, not detected by GWAS, are predicted to include functional variants with larger effects on risk. To identify low frequency coding variants with large effects on LOAD risk, we performed whole exome-sequencing (WES) in 14 large LOAD families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
406
2
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(436 citation statements)
references
References 51 publications
16
406
2
7
Order By: Relevance
“…Overexpression of PLD3 decreased levels of ␤APP, A␤ 42 , and A␤ 40 , whereas PLD3 knockdown increased extracellular A␤ 42 and A␤ 40 [140]. Another study reported that PLD3 was expressed at significantly lower levels in neurons from AD brains compared with non-AD brains [141].…”
Section: Phospholipase Dmentioning
confidence: 98%
See 1 more Smart Citation
“…Overexpression of PLD3 decreased levels of ␤APP, A␤ 42 , and A␤ 40 , whereas PLD3 knockdown increased extracellular A␤ 42 and A␤ 40 [140]. Another study reported that PLD3 was expressed at significantly lower levels in neurons from AD brains compared with non-AD brains [141].…”
Section: Phospholipase Dmentioning
confidence: 98%
“…A third PLD isoform, PLD3, has been recently associated with AD through identification of PLD3 risk variants by whole-exome sequencing and functional studies [140]. Overexpression of PLD3 decreased levels of ␤APP, A␤ 42 , and A␤ 40 , whereas PLD3 knockdown increased extracellular A␤ 42 and A␤ 40 [140].…”
Section: Phospholipase Dmentioning
confidence: 99%
“…3 ). More specifi cally, Val232Met, a putative lossof-function polymorphism, is proposed to increase pathogenic amyloid peptide (A ␤ ) secretion and, hence, increase the risk for late-onset AD ( 81 ). This increased risk is independent of the APOE genotype ( 81 ).…”
Section: Pld3mentioning
confidence: 99%
“…More specifi cally, Val232Met, a putative lossof-function polymorphism, is proposed to increase pathogenic amyloid peptide (A ␤ ) secretion and, hence, increase the risk for late-onset AD ( 81 ). This increased risk is independent of the APOE genotype ( 81 ). Similarly, PLD3 putative loss-of-function polymorphisms have been reported to correlate with increased risk of AD in African Americans ( 81 ).…”
Section: Pld3mentioning
confidence: 99%
See 1 more Smart Citation